2016
DOI: 10.1080/03004430.2016.1203787
|View full text |Cite
|
Sign up to set email alerts
|

Development of the language proficiency of five- to seven-year-olds in rural areas

Abstract: Rural children are a largely understudied population in language and literacy research, despite the fact that these children often enter school with delays in their language development. Since most rural areas suffered from so-called selective rural outmigration, many parents in rural areas are lower or middle educated. The home literacy climate, however, depends not only on the educational level of parents, but also on their lifestyle. In this study, we examined whether parental educational level and literacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In addition, based on the questionnaire, the results showed that the duration of language learning for learners whose mothers are highly educated is longer than that of learners with mothers with lower levels of education. Based on the theory, learners have the opportunity to learn language both in the family and at school for an average of 85 minutes per day (Poolman et al, 2017;Reilly et al, 2020). This skills gap must be overcome by the pre-school literacy program, which must be able to equip parents on how to train their children in language skills and early literacy in their home environment (Krahe et al, 2021;Lane et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, based on the questionnaire, the results showed that the duration of language learning for learners whose mothers are highly educated is longer than that of learners with mothers with lower levels of education. Based on the theory, learners have the opportunity to learn language both in the family and at school for an average of 85 minutes per day (Poolman et al, 2017;Reilly et al, 2020). This skills gap must be overcome by the pre-school literacy program, which must be able to equip parents on how to train their children in language skills and early literacy in their home environment (Krahe et al, 2021;Lane et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Of course, this can help better prepare children for school. Stakeholders must include children who have mothers with lower levels of education into the equalization program for language and literacy learning (Poolman et al, 2017;Reilly et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation